Isolation of Anoxygenic Phototrophic Bacteria from Soil and Water Samples - Saraswathi, R.; Rajani, .B.; Umadevi, M.; Shiva Kumari, C.H.L.P; Shivakumar Singh, P.; Kumaraswamy, T.; Mohan, B. (International Journal of Psychosocial Rehabilitation, 2019)
An oxygenic phototrophic bacterium is the gram-negative bacteria that can use light as an energy source and they are anaerobic as they do not evolve oxygen during photosynthesis. Aerobic an oxygenic phototrophic bacterium is another group of this bacteria which are obligate aerobes that capture energy that light by an oxygenic photosynthesis. Bacterial isolation was done from the soil and water sample collected, followed by the serial dilution and pure cultures were obtained from the cultures grown. Bacteria isolated were purple sulphur bacteria (Chromatium, Ectothiorodospira, Thioapsa), purple non sulphur Bacteria, Green sulphur Bcteria (Chlorobium, Petodictyon, Green Non Sulpher bacteria (Chlorofixus). Were tend to be obtain from the soil and water samples further identification of the bacteria and utilization of Bacteria should be classified in the further studies.